TOPCon battery for improving contact resistance and preparation method thereof
By doping phosphorus in the anti-reflection film on the back of the TOPCon cell to form a laminated silicon nitride film layer, phosphorus is activated to enter the polysilicon layer, which solves the problem of difficult doping control of the polysilicon layer, reduces the contact resistance, and improves the performance of the solar cell. conversion efficiency.
Patent Information
- Application Number
- CN202411444893.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-21
AI Technical Summary
In the existing TOPCon technology, the optical absorption coefficient of the polysilicon/amorphous silicon layer in the N+ layer of the back field is high, resulting in large parasitic absorption, limiting the improvement of solar cell conversion efficiency. At the same time, the thinner polysilicon layer is difficult to control during the doping process, resulting in a decrease in the passivation efficiency of silicon oxide and an increase in contact resistance.
The four layers of silicon -nitride layer are used as the back -reduced reflux, and at least one layer is a silicon -nitrodic membrane layer. By activating the phosphorus in the reducing membrane during high -temperature sintering, it enters the polycrystalline silicon layer, increases the phosphorus doping concentration, increases the difference in the concentration of the two sides of the silicon oxide, and promotes the penetration effect of the carrier.
Effectively reduce the contact resistance, improve the doping control of the polycrystalline silicon layer, and improve the photoelectric conversion efficiency of solar cells.
Smart Images

Figure BDA0005087555530000101 
Figure BDA0005087555530000111 
Figure BDA0005087555530000121
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of photovoltaic cells, and in particular to a TOPCon cell with improved contact resistance and a preparation method thereof. Background Art
[0002] As an emerging energy source, solar cells have been widely used. Among them, TOPCon cells are the mainstream production process direction of high-efficiency solar cells. Various battery manufacturers have conducted extensive research on this process. In order to improve efficiency, various companies have conducted extensive research on this product process. Passivation contact technology is one of its important components. It can obtain a good passivation effect on the surface of silicon wafers, promote electron migration and transmission on the surface of silicon cells, and thus improve the photoelectric conversion efficiency of crystalline silicon solar cells.
[0003] At present, the mainstream back film passivation layer is mainly a silicon nitride stack. The multi-layer silicon nitride structure can well control the coating rate during the deposition process and also retain the passivation effect. The passivation structure can effectively saturate dangling bonds, reduce surface states, reduce surface recombination rates, increase the effective minority carrier lifetime of the battery, obtain higher open circuit voltage and short circuit current, and improve the photoelectric conversion efficiency of solar cells.
[0004] However, in the existing TOPCon technology, the optical absorption coefficient of the polysilicon / amorphous silicon layer in the N+ layer of the back surface field is high. When applied to the surface of the battery, the large parasitic absorption greatly limits the improvement of the battery conversion efficiency. To solve this problem, the industry usually uses thinner polysilicon / amorphous silicon layers. When using thinner polysilicon layers, polysilicon doping is more difficult to control, and the doping source easily penetrates the silicon oxide layer, destroying the silicon oxide passivation efficiency; at the same time, since the doping source penetrates into the surface of the silicon substrate, the substrate doping concentration will increase, the difference in doping concentration on both sides of the silicon oxide layer will decrease, and the probability of carrier tunneling will decrease, causing the contact resistance to increase. Summary of the invention
[0005] In order to solve the above problems, the present application provides a TOPCon battery capable of improving contact resistance, characterized in that it includes: a silicon substrate; the front side of the silicon substrate is provided with a phosphorus-doped region, a front passivation layer, a front anti-reflection film and a front gate line in sequence from the inside to the outside; the back side of the silicon substrate is provided with a tunneling oxide layer, a phosphorus-doped polysilicon layer, a back anti-reflection film and a back gate line in sequence from the inside to the outside; the back anti-reflection film is a four-layer stacked silicon nitride film layer, and at least one layer of the four-layer stacked silicon nitride film layer is a phosphorus-doped silicon nitride film layer.
[0006] In a specific embodiment of the present application, among the four-layer stacked silicon nitride film layers, the inner silicon nitride film layer is preferably a phosphorus-doped silicon nitride film layer.
[0007] In a specific embodiment of the present application, in the four-layer stacked silicon nitride film layer, the refractive index of the silicon nitride film layer gradually decreases from the inside to the outside.
[0008] In a specific embodiment of the present application, in the four-layer stacked silicon nitride film layer, the volume content of phosphorus in each layer of the silicon nitride film layer is 3%-5%.
[0009] In a specific embodiment of the present application, the silicon substrate is an n-type silicon substrate with a thickness of 100-130 μm.
[0010] In a specific embodiment of the present application, the thickness of the back anti-reflection film is 70-80 nm.
[0011] In a specific embodiment of the present application, the refractive index of the back anti-reflection film is 2.12-2.18.
[0012] The present application provides a method for preparing a TOPCon battery, the steps of which include: cleaning and texturing a silicon substrate; performing boron diffusion and alkaline polishing on the texturized substrate; depositing on the back side of the substrate to form a tunneling oxide layer and a phosphorus-doped polysilicon layer; depositing front aluminum oxide and a front anti-reflection film on the front side; depositing a back anti-reflection film on the back side; and screen-printing front and back slurries to make electrodes.
[0013] In a specific embodiment of the present application, a method for preparing the back anti-reflection film of a TOPCon cell is to use a PECVD machine to introduce silane, ammonia and phosphine into the atmosphere for deposition.
[0014] In a specific embodiment of the present application, the flow rate of the phosphine is 1000-2000 sccm, and the concentration of the phosphine is 5%-10%.
[0015] The TOPCon cell provided in the present application can improve the contact resistance. By doping phosphorus in the back anti-reflection film, a phosphorus-doped laminated silicon nitride film layer is formed. The addition of phosphorus will not affect the refractive index and reflectivity of the anti-reflection film. After metallization printing and sintering, the slurry will corrode the anti-reflection film during the high-temperature sintering process. At this time, the phosphorus in the anti-reflection film is activated at high temperature and enters the polysilicon layer, which is equivalent to increasing the phosphorus doping concentration in the polysilicon layer, increasing the difference in doping concentration on both sides of silicon oxide, promoting the quantum tunneling effect of carriers through the Schottky barrier, and improving the ohmic contact of the silver-silicon alloy, resulting in a reduction in contact resistance. The problem of increased contact resistance easily caused by the thinner polysilicon doping in the phosphorus-doped polysilicon layer is improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The accompanying drawings are used to better understand the present application and do not constitute an improper limitation on the present application.
[0017] Figure 1 The TOPCon battery provided by the present application that can improve contact resistance is shown.
[0018] Description of reference numerals:
[0019] 1-front anti-reflection film, 2-front passivation layer, 3-phosphorus-doped region, 4-silicon substrate, 5-tunneling oxide layer, 6-phosphorus-doped polysilicon layer, 7-back anti-reflection film, 8-front gate line, 9-back gate line. DETAILED DESCRIPTION
[0020] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present invention, but the description is based on the general principles of the specification and is not intended to limit the scope of the present invention. The scope of protection of the present invention shall be determined by the attached claims.
[0021] In the art, the side of the silicon-based layer where the PN junction is formed is defined as the front side, and the other side of the silicon-based layer is defined as the back side.
[0022] In this application, under the same temperature, pressure and flow rate, the deposition time is increased by 600-800s, the film thickness and refractive index are measured, and the total film thickness is divided by the time to obtain the deposition rate per second. The deposition time is changed according to the deposition rate per second to obtain the film thickness.
[0023] In the present application, the refractive index is mainly affected by the flow rate ratio of silane to nitrogen. When the flow rate remains unchanged, the measured refractive index is the refractive index corresponding to the flow rate ratio; the refractive index is mainly measured by full-spectrum ellipsometer.
[0024] In this application, the film thickness and refractive index of the product are mainly measured by full-spectrum ellipsometer. This method can be used to verify whether the produced products meet the needs or expectations of the manufacturer, and can also be used to identify the film structure and refractive index of commercially available products.
[0025] See also Figure 1The present application provides a TOPCon cell, which includes a silicon substrate 4, on the front side of which a phosphorus-doped region 3, a front passivation layer 2, a front anti-reflection film 1 and a front gate line 8 are sequentially arranged; on the back side of the silicon substrate 4, a tunneling oxide layer 5, a phosphorus-doped polysilicon layer 6, a back anti-reflection film 7 and a back gate line 9 are sequentially arranged, and the back anti-reflection film 7 is a four-layer stacked silicon nitride film layer.
[0026] In a specific embodiment of the present application, the back anti-reflection film 7 is a four-layer stacked silicon nitride film layer, one of which is a phosphorus-doped silicon nitride film layer.
[0027] In a specific embodiment of the present application, the back anti-reflection film 7 is a four-layer stacked silicon nitride film layer, two of which are phosphorus-doped silicon nitride film layers.
[0028] In a specific embodiment of the present application, the back anti-reflection film 7 is a four-layer stacked silicon nitride film layer, three of which are phosphorus-doped silicon nitride film layers.
[0029] In a specific embodiment of the present application, the back anti-reflection film 7 is a four-layer stacked silicon nitride film layer, wherein four layers are phosphorus-doped silicon nitride film layers.
[0030] In the present application, in the back anti-reflection film 7, when there is a phosphorus-doped silicon nitride film layer in the four-layer stacked silicon nitride film layers, the phosphorus-doped silicon nitride film layer must be arranged close to the phosphorus-doped polysilicon layer 6; when there are multiple phosphorus-doped silicon nitride film layers in the four-layer stacked silicon nitride film layers, the multiple phosphorus-doped silicon nitride film layers must be adjacent to and close to the phosphorus-doped polysilicon layer 6. For example, when there are three phosphorus-doped silicon nitride film layers and one silicon nitride film layer in the four-layer stacked silicon nitride film layers, the silicon nitride film layer is located at the position farthest from the phosphorus-doped polysilicon layer 6 in the four-layer stacked silicon nitride film layers.
[0031] In the present application, in the back anti-reflection film 7 , in the direction from the phosphorus-doped polysilicon layer 6 side to the back gate line 9 side, the refractive index of each layer of the silicon nitride film layer gradually decreases.
[0032] In a specific embodiment of the present application, the silicon substrate 4 is an n-type silicon substrate with a thickness of 100-130μm, for example, it can be 100μm, 101μm, 102μm, 103μm, 104μm, 105μm, 106μm, 107μm, 108μm, 109μm, 110μm, 111μm, 112μm, 113μm, 114μm, 115μm, 116μm, 117μm, 118μm, 119μm, 120μm, 121μm, 122μm, 123μm, 124μm, 125μm, 126μm, 127μm, 128μm, 129μm, 130μm.
[0033] The present application provides a TOPCon cell, wherein the back anti-reflection film 7 of the TOPCon cell is a four-layer stacked silicon nitride film layer, having a phosphorus-doped silicon nitride film layer, the refractive index of the first phosphorus-doped silicon nitride film layer is 2.18-2.22, and the thickness is 10-20nm; the refractive index of the second silicon nitride film layer is 2.15-2.18, and the thickness is 10-15nm; the refractive index of the third silicon nitride film layer is 2.08-2.15, and the thickness is 10-30nm; the refractive index of the fourth silicon nitride film layer is 2.04-2.08, and the thickness is 20-35nm.
[0034] In a specific embodiment of the present application, the back anti-reflection film 7 is a four-layer stacked silicon nitride film layer, and the thickness of the back anti-reflection film 7 is 70-80nm, for example, it can be 70.5nm, 71nm, 71.5nm, 72nm, 72.5nm, 73nm, 73.5nm, 74nm, 74.5nm, 75nm, 75.5nm, 76nm, 76.5nm, 77nm, 77.5nm, 78nm, 78.5nm, 79nm, 79.5nm, 80nm.
[0035] In a specific embodiment of the present application, the back anti-reflection film 7 is a four-layer stacked silicon nitride film layer. According to the refractive index of each layer of the silicon nitride film layer, the refractive index of the back anti-reflection film 7 is 2.12-2.18, for example, it can be 2.12, 2.13, 2.14, 2.15, 2.16, 2.17, 2.18.
[0036] In this field, the refractive index of the four-layer stacked silicon nitride film layer may have some errors due to process reasons. Those skilled in the art should understand that the refractive index of the four-layer stacked silicon nitride film layer has a certain range of variation, that is, as long as the variation of the refractive index of the four-layer stacked silicon nitride film layer is guaranteed, it is not strictly required that the minimum value of the refractive index is 2.12 and the maximum value is 2.18.
[0037] The present application provides a method for preparing a TOPCon battery, the steps of which include:
[0038] (1) Texturing: N-type silicon wafers are used, 1% alkali solution is used for texturing, and hydrogen peroxide and alkali are used to clean the silicon wafers;
[0039] (2) Boron diffusion: A tubular boron diffusion furnace is used to maintain the temperature at 800-880°C and BCl3 / BBr3 is used as a boron source to introduce P-type element boron (B) into the silicon wafer, thereby forming a PN junction inside the silicon wafer;
[0040] (3) Alkali polishing: Use a chain HF machine to remove the BSG on the back side, and then use a slot-type alkaline polishing machine to remove the PN junction on the back side and the edge;
[0041] (4) The main steps of the Poly process are as follows:
[0042] Deposition 1: Nitrous oxide (N2O) is introduced to form a 1-2 nm oxide layer on the polished back structure; Deposition 2: Silane (SiH4), phosphine (PH3), and hydrogen (H2) are introduced to deposit about 70-90 nm of phosphorus-doped amorphous silicon;
[0043] Oxidation: introducing silane (SiH4) and nitrous oxide (N2O) to form a 5-15nm SiO2 mask on the surface of phosphorus-doped amorphous silicon; (5) Crystallization annealing: using a tubular annealing furnace, using nitrogen (N2) or oxygen (O2) to transform the crystal structure of the deposited amorphous silicon film to form a polycrystalline silicon film Poly-Si;
[0044] (6) RCA cleaning: first, a chain HF machine is used to remove the s-tunneling oxide layer 5 that is plated around the front surface during deposition in step (6) and the mask layer generated during the annealing process, and then a slot machine is used to remove the phosphorus-doped area 3 on the front surface and the front mask layer formed in step (2);
[0045] (7) Deposition of the front passivation layer 2 and the front anti-reflection film 1: 4-6 nm aluminum oxide (AlO x ) film is used for passivation, and 70-80nm silicon nitride (SiNx) film is deposited by PECVD for anti-reflection;
[0046] (8) Deposition of back anti-reflection film 7: SiN is deposited by PECVD xThe film is deposited at a temperature of 450°C to 550°C, a silane flow rate of 1200-2500sccm, an ammonia flow rate of 5000-15000sccm, a phosphine flow rate of 1000-2000sccm, a deposition time of 100-130s, a pressure of 200-250Pa, a power of 9000-15000W, a duty cycle of (3-6): (50-100), and a first phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.18-2.22 and a thickness of 10-20nm is obtained; the deposition temperature is maintained at 450° C. to 550° C., the flow rate of silane is 1200-2500 sccm, the flow rate of ammonia is 4000-10000 sccm, the flow rate of phosphine is 1000-2000 sccm, the deposition time is 100-130 s, the pressure is 200-250 Pa, the power is 9000-15000 W, the duty cycle is (3-6): (50-100), and a second phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.15-2.18 and a thickness of 10-15 nm is obtained; the deposition temperature is maintained at 450° C. to 550° C., The silane flow rate is 1200-2500sccm, the ammonia flow rate is 5000-15000sccm, the phosphine flow rate is 1000-2000sccm, the deposition time is 120-200s, the pressure is 200-250Pa, the power is 9000-15000W, the duty cycle is (3-6): (50-100), and a third phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.08-2.15 and a thickness of 10-30nm is obtained; the deposition temperature is maintained at 450°C to 550°C, the silane flow rate is 120 0-2500sccm, ammonia flow rate 5000-15000sccm, phosphine flow rate 1000-2000sccm, deposition time 250-300s, pressure 200-250Pa, power 9000-15000W, duty cycle (3-6): (50-100), to obtain a fourth phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.04-2.08 and a thickness of 20-35nm, constituting a back phosphorus-doped anti-reflection film with a total thickness of 72-78nm and a total refractive index of 2.12-2.18.
[0047] (9) Screen printing the front and back slurries to make electrodes;
[0048] (10) Light injection, test efficiency and sorting.
[0049] In a specific embodiment of the present application, the preparation method of the back side anti-reflection film 7 is: when preparing the back side anti-reflection film 7, silane, ammonia and phosphine gases are introduced into the atmosphere at the same time, and deposited on the surface of the phosphorus-doped polysilicon layer 6, and the deposition equipment includes but is not limited to a PECVD machine or other equipment with deposition function known to those skilled in the art.
[0050] In the present application, the method of doping phosphorus in the back anti-reflection film 7 can also be applied to batteries with other structures, thereby improving the contact resistance of existing or future batteries with different structures.
[0051] Example 1
[0052] This embodiment provides a method for preparing a TOPCon battery with improved contact resistance, the steps of which include:
[0053] (1) Texturing: N-type silicon wafers are used, 1% alkali solution is used for texturing, and hydrogen peroxide and alkali are used to clean the silicon wafers;
[0054] (2) Boron diffusion: A tubular boron diffusion furnace is used to maintain the temperature at 800-880°C and BCl3 / BBr3 is used as a boron source to introduce P-type element boron (B) into the silicon wafer, thereby forming a PN junction inside the silicon wafer;
[0055] (3) Alkali polishing: Use a chain HF machine to remove the BSG on the back side, and then use a slot-type alkaline polishing machine to remove the PN junction on the back side and the edge;
[0056] (4) The main steps of the Poly process are as follows:
[0057] Deposition 1: Nitrous oxide (N2O) is introduced to form a 1.5 nm tunneling oxide layer 5 on the polished back surface structure;
[0058] Deposition 2: Pass silane (SiH4), phosphine (PH3), and hydrogen (H2) to deposit about 80nm of phosphorus-doped amorphous silicon;
[0059] Oxidation: Silane (SiH4) and laughing gas (N2O) are introduced to form a 10nm SiO2 mask on the surface of phosphorus-doped amorphous silicon;
[0060] (5) Crystallization annealing: A tubular annealing furnace is used to transform the crystal structure of the deposited amorphous silicon film using nitrogen (N2) or oxygen (O2) to form a polycrystalline silicon film Poly-Si;
[0061] (6) RCA cleaning: first, a chain HF machine is used to remove the tunneling oxide layer 5 that is plated around the front surface during deposition in step (6) and the mask layer generated during the annealing process, and then a slot machine is used to remove the phosphorus-doped area 3 on the front surface and the front mask layer formed in step (2);
[0062] (7) Deposition of the front passivation layer 2 and the front anti-reflection film 1: A 5 nm aluminum oxide (AlOx) film is deposited by ALD for passivation, and a 75 nm silicon nitride (SiNx) film is deposited by PECVD for anti-reflection;
[0063] (8) Deposition of back anti-reflection film 7: SiN is deposited by PECVD xThe film was deposited at a temperature of 450°C to 550°C, with a silane flow rate of 2500sccm, an ammonia flow rate of 10000sccm, a phosphine flow rate of 1000sccm, a deposition time of 110s, a pressure of 220Pa, a power of 12500W, and a duty cycle of 6:95 to obtain a first phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.22 and a thickness of 10nm; the deposition temperature was maintained at a temperature of 450°C to 550°C, with a silane flow rate of 2000sccm, an ammonia flow rate of 10000sccm, a deposition time of 130s, a pressure of 220Pa, a power of 12500W, and a duty cycle of 6:90 to obtain a second silicon nitride anti-reflection film with a refractive index of 2.16 and a thickness of 15nm ; The deposition temperature is maintained at 450°C to 550°C, the silane flow rate is 1500sccm, the ammonia flow rate is 12000sccm, the deposition time is 190s, the pressure is 220Pa, the power is 12500W, the duty cycle is 5:70, and a third silicon nitride anti-reflection film with a refractive index of 2.1 and a thickness of 25nm is obtained; the deposition temperature is maintained at 450°C to 550°C, the silane flow rate is 1200sccm, the ammonia flow rate is 15000sccm, the deposition time is 285s, the pressure is 220Pa, the power is 12500W, the duty cycle is 5:70, and a fourth silicon nitride anti-reflection film with a refractive index of 2.04 and a thickness of 25nm is obtained, constituting a back-side phosphorus-doped anti-reflection film with a total thickness of 75nm.
[0064] (9) Screen printing the front and back slurries to make electrodes;
[0065] (10) Light injection, test efficiency and sorting.
[0066] Example 2
[0067] This embodiment provides a method for preparing a TOPCon battery with improved contact resistance, and the steps thereof are different from those in Embodiment 1 in that:
[0068] Back anti-reflection film 7 deposition: SiN is deposited by PECVD xThe film was deposited at a temperature of 450°C to 550°C, with a silane flow rate of 2500sccm, an ammonia flow rate of 10000sccm, a phosphine flow rate of 1000sccm, a deposition time of 100s, a pressure of 220Pa, a power of 12500W, and a duty cycle of 6:95 to obtain a first phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.22 and a thickness of 10nm; the deposition temperature was maintained at a temperature of 450°C to 550°C, with a silane flow rate of 2000sccm, an ammonia flow rate of 10000sccm, a phosphine flow rate of 1200sccm, a deposition time of 120s, a pressure of 220Pa, a power of 12500W, and a duty cycle of 6:90 to obtain a second phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.16 and a thickness of 15nm Phosphorus-doped silicon nitride anti-reflection film; the deposition temperature is maintained at 450°C to 550°C, the silane flow rate is 1500sccm, the ammonia flow rate is 12000sccm, the deposition time is 190s, the pressure is 220Pa, the power is 12500W, the duty cycle is 5:70, and a third silicon nitride anti-reflection film with a refractive index of 2.1 and a thickness of 25nm is obtained; the deposition temperature is maintained at 450°C to 550°C, the silane flow rate is 1200sccm, the ammonia flow rate is 15000sccm, the deposition time is 285s, the pressure is 220Pa, the power is 12500W, the duty cycle is 5:70, and a fourth silicon nitride anti-reflection film with a refractive index of 2.04 and a thickness of 25nm is obtained, constituting a back-side phosphorus-doped anti-reflection film with a total thickness of 75nm.
[0069] (9) Screen printing the front and back slurries to make electrodes;
[0070] (10) Light injection, test efficiency and sorting.
[0071] Example 3
[0072] This embodiment provides a method for preparing a TOPCon battery with improved contact resistance, and the steps thereof are different from those in Embodiment 1 in that:
[0073] Back anti-reflection film 7 deposition: SiN is deposited by PECVD xThe film is deposited at a temperature of 450°C to 550°C, with a silane flow rate of 2500sccm, an ammonia flow rate of 10000sccm, a phosphine flow rate of 1000sccm, a deposition time of 100s, a pressure of 220Pa, a power of 12500W, and a duty cycle of 6:95 to obtain a first phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.22 and a thickness of 10nm; the deposition temperature is maintained at a temperature of 450°C to 550°C, with a silane flow rate of 2000sccm, an ammonia flow rate of 10000sccm, a phosphine flow rate of 1200sccm, a deposition time of 120s, a pressure of 220Pa, a power of 12500W, and a duty cycle of 6:90 to obtain a second phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.16 and a thickness of 15nm ; The deposition temperature is maintained at 450°C to 550°C, the silane flow rate is 1500sccm, the ammonia flow rate is 12000sccm, the phosphine flow rate is 1500sccm, the deposition time is 175s, the pressure is 220Pa, the power is 12500W, the duty cycle is 5:70, and a third phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.1 and a thickness of 25nm is obtained; the deposition temperature is maintained at 450°C to 550°C, the silane flow rate is 1200sccm, the ammonia flow rate is 15000sccm, the deposition time is 285s, the pressure is 220Pa, the power is 12500W, the duty cycle is 5:70, and a fourth silicon nitride anti-reflection film with a refractive index of 2.04 and a thickness of 25nm is obtained, constituting a back-side phosphorus-doped anti-reflection film with a total thickness of 75nm.
[0074] Example 4
[0075] This embodiment provides a method for preparing a TOPCon battery with improved contact resistance, and the steps thereof are different from those in Embodiment 1 in that:
[0076] Back anti-reflection film 7 deposition: SiN is deposited by PECVD xThe film is deposited at a temperature of 450°C to 550°C, with a silane flow rate of 2500sccm, an ammonia flow rate of 10000sccm, a phosphine flow rate of 1000sccm, a deposition time of 100s, a pressure of 220Pa, a power of 12500W, and a duty cycle of 6:95 to obtain a first phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.22 and a thickness of 10nm; the deposition temperature is maintained at a temperature of 450°C to 550°C, with a silane flow rate of 2000sccm, an ammonia flow rate of 10000sccm, a phosphine flow rate of 1200sccm, a deposition time of 120s, a pressure of 220Pa, a power of 12500W, and a duty cycle of 6:90 to obtain a second phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.16 and a thickness of 15 ... At 450°C to 550°C, the silane flow rate is 1500sccm, the ammonia flow rate is 12000sccm, the phosphine flow rate is 1500sccm, the deposition time is 175s, the pressure is 220Pa, the power is 12500W, and the duty cycle is 5:70, to obtain a third phosphorus-doped silicon nitride anti-reflection film with a refractive index of 2.1 and a thickness of 25nm; the deposition temperature is maintained at 450°C to 550°C, the silane flow rate is 1200sccm, the ammonia flow rate is 15000sccm, the phosphine flow rate is 1800sccm, the deposition time is 275s, the pressure is 220Pa, the power is 12500W, and the duty cycle is 5:70, to obtain a fourth silicon nitride anti-reflection film with a refractive index of 2.04 and a thickness of 25nm, constituting a back-side phosphorus-doped anti-reflection film with a total thickness of 75nm.
[0077] Comparative Examples 1-4 adopt the prior art, i.e., Examples 1-4 in Chinese Patent CN116137299A, and the data in Tables 1 and 2 below are extracted accordingly.
[0078] Comparative Example 5
[0079] This comparative example provides a method for preparing a TOPCon battery, the steps of which are different from those of Example 1 in that:
[0080] Back anti-reflection film 7 deposition: SiN is deposited by PECVD xThe film was deposited at a temperature of 450°C to 550°C, with a silane flow rate of 2500sccm, an ammonia flow rate of 10000sccm, a deposition time of 100s, a pressure of 220Pa, a power of 12500W, and a duty cycle of 6:95 to obtain a first silicon nitride anti-reflection film with a refractive index of 2.22 and a thickness of 10nm; the deposition temperature was maintained at 450°C to 550°C, with a silane flow rate of 2000sccm and an ammonia flow rate of 10000sccm. m, deposition time 120s, pressure 220Pa, power 12500W, duty cycle 6:90, to obtain a second silicon nitride anti-reflection film with a refractive index of 2.16 and a thickness of 15nm; the deposition temperature was maintained at 450℃ to 550℃, the silane flow rate was 1500sccm, the ammonia flow rate was 12000sccm, the deposition time was 190s, the pressure was 220Pa, the power was 12500W, the duty cycle was 5:70, and the refractive index was 2.1, A third silicon nitride anti-reflection film with a thickness of 25nm; the deposition temperature is maintained at 450°C to 550°C, the silane flow rate is 1200sccm, the ammonia flow rate is 15000sccm, the deposition time is 285s, the pressure is 220Pa, the power is 12500W, the duty cycle is 5:70, and a fourth silicon nitride anti-reflection film with a refractive index of 2.04 and a thickness of 25nm is obtained, forming a back anti-reflection film 7 with a total thickness of 75nm; and a 18nm fifth film is deposited. body, refractive index 1.86, silane flow rate 950sccm, ammonia flow rate 15500sccm, deposition time 270s, pressure 130Pa, power 11000W, duty cycle 6:96; finally, a sixth film body is deposited on the surface with a thickness of 15nm, a refractive index 1.45, a silane flow rate of 750sccm, an ammonia flow rate of 15500sccm, a deposition time 210s, pressure 130Pa, power 11000W, and duty cycle 6:90.
[0081] Comparative Example 6
[0082] This comparative example provides a method for preparing a TOPCon cell, the steps of which are different from those of Example 1 in that phosphorus is not doped in the anti-reflection film.
[0083] Table 1 Anti-reflection film structures of various embodiments and comparative examples
[0084]
[0085]
[0086] Note: The symbol “\” indicates that the film layer structure does not exist in the embodiment or comparative example.
[0087] Table 2 Performance of batteries obtained in various embodiments and comparative examples
[0088]
[0089] The parameters of Examples 1-4 and Comparative Examples 1-6 are shown in Table 2, wherein the conversion efficiency Eta, open circuit voltage Uoc, short circuit current Isc, fill factor FF, leakage current IRev2, series resistance Rs and parallel resistance Rsh are obtained by testing with a halm tester under standard calibration; the contact resistance is obtained by testing with a release resistance tester using the TLM method.
[0090] From Examples 1-4 combined with Comparative Example 6, it can be found that when phosphorus is doped into the back anti-reflection film 7, the contact resistance of the battery is reduced.
[0091] From Examples 1-4 and Comparative Example 5, it can be found that when the back anti-reflection film 7 has 4 layers or less, the contact resistance of the battery is low, but when the back anti-reflection film 7 has 6 layers, the contact resistance of the battery increases.
[0092] From Examples 1-4 and Comparative Examples 1-4, it can be found that the effect of doping phosphorus in the back anti-reflection film 7 is much better than that of doping phosphorus in the front anti-reflection film 1.
Claims
1. A TOPCon battery, characterized in that: include: Silicon substrate; A phosphorus-doped region, a front passivation layer, a front anti-reflection film and a front gate line are sequentially arranged on the front side of the silicon substrate; A tunneling oxide layer, a phosphorus-doped polysilicon layer, a back anti-reflection film and a back gate line are sequentially arranged on the back side of the silicon substrate; The back anti-reflection film is a four-layer stacked silicon nitride film layer, and at least one layer of the four-layer stacked silicon nitride film layer is a phosphorus-doped silicon nitride film layer.
2. The TOPCon battery according to claim 1, characterized in that In the four-layer stacked silicon nitride film layer, the silicon nitride film layer close to the phosphorus-doped polysilicon layer is a phosphorus-doped silicon nitride film layer.
3. The TOPCon battery according to claim 1, characterized in that In the four-layer stacked silicon nitride film layers, the refractive index of each layer of the silicon nitride film layer gradually decreases in the direction from the phosphorus-doped polysilicon layer side to the back gate line side.
4. The TOPCon battery according to claim 1, characterized in that In the four-layer stacked silicon nitride film layers, the volume content of phosphorus in each layer of the silicon nitride film layer is 3%-5%.
5. The TOPCon battery according to claim 1, characterized in that The silicon substrate is an n-type silicon substrate with a thickness of 100-130 μm.
6. The TOPCon battery according to claim 1, characterized in that The thickness of the back anti-reflection film is 70-80 nm.
7. The TOPCon battery according to claim 1, characterized in that The refractive index of the back anti-reflection film is 2.12-2.
18.
8. The method for preparing a TOPCon battery according to any one of claims 1 to 7, characterized in that the steps include: Cleaning and texturing the silicon substrate; The substrate after texturing is subjected to boron diffusion and alkali polishing treatment; Deposition is performed on the back side of the substrate to form a tunnel oxide layer and a phosphorus-doped polysilicon layer; Depositing front aluminum oxide and front anti-reflection film on the front side; Depositing a back anti-reflection film on the back side; Screen print the front and back paste to make electrodes.
9. The method according to claim 8, characterized in that The method for preparing the back anti-reflection film comprises: Silane, ammonia and phosphine were introduced into the atmosphere by a PECVD machine for deposition.
10. The method according to claim 9, characterized in that The flow rate of the phosphine is 1000-2000 sccm, and the concentration of the phosphine is 5%-10%.
Citation Information
Patent Citations
Solar cell and preparation method thereof
CN116137299A